Consumers’ Decision on Perspective of Rationality Economics and Willingness to Demand Health Insurance - Tachhekar, Isha; Khadka, Chakra Bahadur (Economic Journal of Development Issues, 2020)
Behavioral economics responds that individuals frequently do not act rationally in the economic logic. This research specifies a review of behavioral economics and shows the use in health care to improve individuals’ decisions and demand for health insurance. The purpose of this study is to examine the factors of consumer behavior that impact their perception of health insurance and their willingness to purchase health insurance. The data collection is performed through an internet survey with the use of a self-administered questionnaire comprising ranking and Likert scale questions. Data has been reduced using a random mapping supplementary method. The original accuracy final dimensionality is sufficiently large and thus only 100 sample sizes have been used. The data was analyzed through different descriptive statistical tools and structural equation modeling was used to show the causal relationship between the identified variables. Most of the identified factors were expected to significantly impact the consumer’s willingness to purchase. Among the factors, the most important factor was found to be the consumer’s perception which was found to have a significant mediation role on features of the policy, attributes of the company, and governmental role. Also, there was found to be a significant mediation role of individual background on the relationship between personal perception and willingness to purchase health insurance. In conclusion, insurance companies and the government should take a joint initiative in conducting awareness programson risk management through health insurance. The existing health insurance products should be redesigned focusing on the perpetual factors that increase the likelihood of willingness to purchase. The government should actively monitor insurance practitioners to control as well as innovate suitable, adequate, and affordable health insurance plans.